2013
DOI: 10.1167/13.3.32
|View full text |Cite
|
Sign up to set email alerts
|

Positional priming of pop-out is nested in visuospatial context

Abstract: The present study investigated facilitatory and inhibitory positional priming using a variant of Maljkovic and Nakayama's (1996) priming of pop-out task. Here, the singleton target and the distractors could be presented in different visuospatial contexts-but identical screen locations-across trials, permitting positional priming based on individual locations to be disentangled from priming based on interitem configural relations. The results revealed both significant facilitatory priming, i.e., faster reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 57 publications
(92 reference statements)
2
13
0
1
Order By: Relevance
“…By this account, priming only lasts for roughly eight trials-in contrast to the long-term effects of contextual cueing-because a stable association between the spatial configuration and a specific target location never develops. A complementary prediction, made by Geyer et al, is that priming would suffer if the spatial configurations were varied from trial to trial, which is indeed what they found, supporting a linkage between the two spatial phenomena (Geyer et al, 2007; see also Gokce, Müller, & Geyer, 2013). If one considers configuration repetitions as repetitions of an object structure, this study also lends support for spatial priming occurring within an object-centered frame of reference, although this condition is more analogous to our combined retino/spatio/object-centered priming condition.…”
Section: If Priming Is Adaptive Why Isn't It Optimal?supporting
confidence: 53%
“…By this account, priming only lasts for roughly eight trials-in contrast to the long-term effects of contextual cueing-because a stable association between the spatial configuration and a specific target location never develops. A complementary prediction, made by Geyer et al, is that priming would suffer if the spatial configurations were varied from trial to trial, which is indeed what they found, supporting a linkage between the two spatial phenomena (Geyer et al, 2007; see also Gokce, Müller, & Geyer, 2013). If one considers configuration repetitions as repetitions of an object structure, this study also lends support for spatial priming occurring within an object-centered frame of reference, although this condition is more analogous to our combined retino/spatio/object-centered priming condition.…”
Section: If Priming Is Adaptive Why Isn't It Optimal?supporting
confidence: 53%
“…Prior research had shown that position priming is largely independent of color priming (e.g., Maljkovic and Nakayama, 1996; Gokce et al, 2013), but may interact with response priming, particularly when response speed is low (e.g., Lamy et al, 2010). Given this, positional priming may be affected by repetitions versus changes of observers’ overt search task response.…”
Section: Resultsmentioning
confidence: 99%
“…g . , G e y e r, M ü l l e r, & Krummenacher, 2007;Gokce et al, 2013). As such, it may be possible, for example, to shift the eye and all stimuli in the scene the same distance in between trials and still obtain response-dependent spatial priming.…”
Section: Discussionmentioning
confidence: 99%
“…Simply, if target-target spatial priming is positive when the response repeats and weaker, reversed or nonexistent when the response switches, the claim can be made that the target-target priming effect is mainly or exclusively on postselective processes. Other processes that are commonly linked to attention may play a much smaller role (e.g., Gokce et al, 2014;Gokce et al, 2013Gokce et al, , 2015.…”
mentioning
confidence: 99%